2013
DOI: 10.1155/2013/976034
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Application of a New Reversed Phase HPLC Method forIn VitroDissolution Studies of Rabeprazole Sodium in Delayed-Release Tablets

Abstract: The purpose of this study was to develop and validate a new reversed phase high performance liquid chromatographic (RP-HPLC) method to quantify in vitro dissolution assay of rabeprazole sodium in pharmaceutical tablet dosage form. Method development was performed on C 18, 100 × 4.6 mm ID, and 10 μm particle size column, and injection volume was 20 μL using a diode array detector (DAD) to monitor the detection at 280 nm. The mobile phase consisted of buffer: acetonitrile at a ratio of 60 : 40 (v/v), and the flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Drug solubility and solution stability are important properties to be considered when selecting the dissolution medium 32 . It is still important for good water solubility drugs to keep the stability in physiology dissolution media with pH range from 1.0 to 6.8, although some research 3 , 32 have reported that high pH media such as pH 7.5 PBS, pH 8.0 Tris buffer, and pH 9.0 borate buffer were used for dissolution testing to assess the enteric properties of RAB-coated tablets. High pH dissolution media can be used for quality control of oral solid dosage form of RAB, but little in vitro–in vivo correlation can be afforded from the aspect of Biopharmaceutics Classification System (BCS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drug solubility and solution stability are important properties to be considered when selecting the dissolution medium 32 . It is still important for good water solubility drugs to keep the stability in physiology dissolution media with pH range from 1.0 to 6.8, although some research 3 , 32 have reported that high pH media such as pH 7.5 PBS, pH 8.0 Tris buffer, and pH 9.0 borate buffer were used for dissolution testing to assess the enteric properties of RAB-coated tablets. High pH dissolution media can be used for quality control of oral solid dosage form of RAB, but little in vitro–in vivo correlation can be afforded from the aspect of Biopharmaceutics Classification System (BCS).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in the treatment of active peptic ulcers, severe gastro-oesophageal reflux disease (GERD) and Zollinger-Ellison syndrome through suppressing the gastric acid secretion 2–4 . Because it rapidly degrades in acid media and is more stable under alkaline conditions 3 , RAB is usually prepared into enteric-coated dosage forms such as pellets, capsules, and tablets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2) It is widely used for the treatment of active peptic ulcers, severe gastroesophageal reflux disease (GERD), and Zollinger-Ellison syndrome by suppressing gastric acid secretion. [2][3][4] From a pharmaceutical point of view, lansoprazole is assigned to class II drugs having low solubility and high permeability according to the biopharmaceutical classification system; it is a weak base (pK a =8.87) and poorly soluble in water (3.2×10 −2 mg/mL at pH 7.0 and 25°C). Furthermore, lansoprazole is an acid-labile drug by nature 3) ; thus, an enteric coating (pH-dependent coating) is essential for the oral dosage form.…”
mentioning
confidence: 99%